EU crisis management after Lisbon a new model to address security challenges in the 21st century? - Pirozzi, Nicoletta (Intersentia, 2015)
This book analyzes the approach of the European Union (EU) to crisis management in the aftermath of the entry into force of the Lisbon Treaty and assesses its suitability to address current and future security threats. It primarily provides a framework of analysis to interpret current EU crisis management as both a product of the innovations of the Lisbon Treaty and its interaction with the international security environment. It also offers a comprehensive and in-depth examination of post-Lisbon crisis management system in terms of concepts, structures, process and capabilities. 0A reality check of this system is conducted through the analysis of a number of case studies where the EU recently exhibited its crisis management role: the civilian missions EUCAP Sahel Niger, EUCAP Nestor and EUAVSEC South Sudan, and the military operation EUTM Mali. This analysis sheds light on the modalities selected by the EU to intervene in crisis situations, the impact that its interventions have produced in those cases and the lessons that the EU has learnt from these experiences